Gambaran Waktu Tunggu Pelayanan Resep Non Racikan di Instalasi Farmasi Rawat Jalan Rumah Sakit X Sidoarjo pada Bulan Maret Tahun 2019. - Abdul Ghani Rizky rahadianto; Andri Priyoherianto (Akademi Farmasi Mitra Sehat Mandiri Sidoarjo, 2021)
One of the standard pharmaceutical services in hospitals is waiting time. The waiting time for the drug service is the grace period for the patient to submit the prescription until receiving the drug. Waiting time has an effect on service quality and patient satisfaction. This study aims to evaluate the implementation of Hospital Minimum Service Standards (SPM) with the types of pharmacy services in the old category of waiting time for outpatient prescription services at Sidoarjo X Hospital. This research is a non-experimental study with a descriptive design for patients with outpatient cooperative insurance prescriptions in Pharmacy Hospital Sidoarjo Hospital and sampling using the probability sampling method, namely simple random sampling. The time of the study was in March 2019. The calculation of the waiting time for prescription drug services was carried out and then an analysis of the suitability of service standards was carried out with a minimum length of time waiting category The number of recipes examined in this study were 379 prescriptions which were prescriptions for finished or non-concocted drugs. The average waiting time for finished or non-concocted drugs is 18.66 minutes. This is in accordance with the minimum service standards required by Kepmenkes No.129 / Menkes / SK / II / 2008 concerning prescription services for both finished drugs and concoction drugs, namely the length of waiting time for finished drugs ≤30 minutes and concoction drugs ≤60 minutes, and from the average sample studied there was no longer the waiting time as required.